Visitor satisfaction with a key wildlife tourism destination within the context of a damaged landscape. Issue 6 (3rd April 2019) - Newsome, D.; Rodger, K.; Pearce, J.; Chan, K.L.J.
Abstract : Wildlife tourism is a growing industry globally and visitor satisfaction is vital to ensure its long-term sustainability. The Lower Kinabatangan River is a premier wildlife tourism destination that is affected by surrounding land uses and needs careful management to ensure it continues to provide positive wildlife tourism experiences. As little is known about the motivations and satisfaction of tourists with this experience, a visitor survey was conducted along the Lower Kinabatangan River with 346 surveys completed. The attribute 'Interest in viewing wildlife' had the highest mean level of importance and satisfaction (mean = 4.54 and 4.1, respectively, on a 5-point scale). Respondents were very satisfied with their wildlife tour experience (85%) and would recommend the experience to their friends (87%). However, almost half of respondents (47%) felt more needed to be done to protect the Kinabatangan River and wildlife. Although respondents were satisfied overall with their experience, they also expressed concerns over the number of boats and the protection of the River. Comments focused on the presence of rubbish in the River, intrusion of oil palm and the loss of forest. Many issues are beyond the management realms of tour operators but will impact on the future of the industry.